Perancangan Ulang UI/UX Website SMA Negeri 2 Banguntapan dengan Metode Design Thinking - Seto Herlambang; Herlina; Benyamin L.Sinaga (Universitas Atma Jaya Yogyakarta, 2024)
Websites in the educational context play an important role in accessing educational resources, which must be followed by educational institutions, including SMA N 2 Banguntapan. Based on the results of evaluations and structured interviews on the SMA N 2 Banguntapan website, problems are currently found, such as low usability and the level of user satisfaction. the low one. This experimental research is redesigning the UI/UX of the SMA N 2 Banguntapan website that the school's students expect using the Design Thinking method. Based on the research that has been carried out as a whole, the final evaluation results were positive. The SUS evaluation obtained a score in the grade category